Mathematics Self-Efficacy of Brazilian High School Students: A Mixed-Methods Approach Study - Iaochite, Roberto Tadeu [UNESP]; da Matos, Mayara Mota; da Costa Filho, Roraima Alves [UNESP]; Azzi, Roberta Gurgel [UNESP]; Maciel, Ana Cecília de Medeiros (Wiley, 2025)
This study examines the mathematics self-efficacy of 833 high school students from four Brazilian public schools. Using an exploratory cross-sectional design with a mixed-methods approach, students completed online instruments including a sociodemographic questionnaire, scales measuring various self-efficacy domains (mathematics, self-regulated learning, social and emotional) and open-ended questions about their perceived attributes in learning mathematics. Multiple regression analysis revealed that student characteristics and self-efficacy domains collectively explained 47.4% of the variance in mathematics self-efficacy. Qualitative analysis revealed the complex nature of mathematics self-efficacy, emphasising students' perceptions of their strengths and weaknesses in learning. The study underscores the significant influence of student characteristics and self-efficacy domains, highlighting the importance of mixed-methods approaches for deeper insights and guiding future educational interventions.
Keywords: high school students; mathematics self-efficacy; mixed methods; self-regulated learning